Developing fun e-modules for engaging English learning in primary school - Lasim Muzammil; Maria Purnawati; A. Andy; Finda Hikmah Arifani (Universitas Muhammadiyah Malang, 2024)
Teaching material modules in English for primary school can be easily obtained as it is already included in the digital era. However, finding appropriate ones for the instructional process for learners whose internet connection is difficult remains low. Therefore, this research aims to produce a valid and feasible English E-module as a learning medium. The ADDIE approach is used, which stands for analysis, design, development, implementation, and evaluation. The study tested validity by material, media, and language validators to determine the quality of the media developed. The results of this study are that the overall average validation of material is 77.2%, media validation is 78.5%, and language validation gets 87.5% with the